Is more really better? Performance measure variety and environmental uncertainty. Issue 6 (3rd August 2020) - Rikhardsson, Pall; Wendt, Stefan; Arnardóttir, Auður Arna; Sigurjónsson, Throstur Olaf
Abstract : Purpose: This paper asks the question of whether more environmental uncertainty affects the design of performance measurement systems in terms of a greater variety of performance measures and whether this leads to more management satisfaction with the performance measurement system and improved firm performance. Design/methodology/approach: Information processing theory is used to frame the hypotheses and findings. A questionnaire was sent to the 300 largest companies in Iceland, where environmental uncertainty has been prevalent. Findings: The results indicate that increased uncertainty leads to a larger variety of non-financial performance measures, such as customer measures. A positive relationship is found between management satisfaction with the performance measurement system and firm performance. However, the variety of performance measures was not linked to management satisfaction or firm performance. Research limitations/implications: The results suggest that managers increase the variety of performance measures when uncertainty increases. However, it is not the variety itself that increases management satisfaction or improves firm performance. Practical implications: Performance measurement design is affected by environmental uncertainty. Managers focus on important stakeholder groups such as customers under such conditions and can consult research and practice for the purpose of customer relationship management and customer profitability measurement to improve measurement selection. Originality/value: This work focusses on performance measurement system design, examining the use of more than 50 different performance measures, and differentiates between small and medium-sized firms and between service and non-service firms.